Prenatal care in the primary health care network in FortalezaCE: an assessment of the structure, process and results - Rebeca Silveira Rocha; Marcelo Gurgel Carlos da Silva (Universidade de Fortaleza, 2012)
Objective: To evaluate the prenatal care assistance in the primary health care network in Fortaleza-CE, considering the structure, process and results. Methods: A cross sectional descriptive study, of quantitative approach, performed between October 2009 and February 2011, in 30 Health Units randomly selected, keeping the ratio for each Regional Executive Secretary. For analysis of the structure, the information obtained was scored and classified as: excellent, satisfactory, precarious or insufficient. The form used was submitted to four experts for validation. In evaluating the process and results, data was available by the Municipal Health Secretary of Fortaleza for obtainance of the indicators recommended by the Ministry of Health. Results: There was, in general, a satisfactory structure. As for the process and result, we obtained: pregnant women who had, at least, six prenatal visits (7.6%); pregnant women who received tetanus immunization (22.8%); newborns with congenital syphilis (1.4%); newborns with neonatal tetanus (0%); maternal mortality rate (78.5% in 2008 and 51% in 2009) and total neonatal mortality rate (10.1% in 2008 and 11.2% in 2009). Conclusions: Despite good results with regard to the structure, the reflections on the process and outcome indicators were not positive, with low rates compared to those expected by the World Health Organization or the Ministry of Health, or in comparison with other regions.